Current Challenges of Mitochondrial Potassium Channel Research - Kulawiak, Bogusz; Szewczyk, Adam (Frontiers in Physiology, 2022)
In this paper, the current challenges of mitochondrial potassium channels research were critically reviewed. Even though recent progress in understanding K+ traffic in mitochondria has been substantial, some basic issues of this process remain unresolved. Here, we focused on the critical discussion of the molecular identity of various mitochondrial potassium channels. This point helps to clarify why there are different potassium channels in specific mitochondria. We also described interactions of mitochondrial potassium channel subunits with other mitochondrial proteins. Posttranslational modifications of mitochondrial potassium channels and their import are essential but unexplored research areas. Additionally, problems with the pharmacological targeting of mitochondrial potassium channel were illustrated. Finally, the limitation of the techniques used to measure mitochondrial potassium channels was explained. We believe that recognizing these problems may be interesting for readers but will also help to progress the field of mitochondrial potassium channels.